The use of routine EEG in acute ischemic stroke patients without seizures: generalized but not focal EEG pathology is associated with clinical deterioration. (4th May 2017) - Wolf, Marc E.; Ebert, Anne D.; Chatzikonstantinou, Anastasios
Abstract : Purpose : Specialized electroencephalography (EEG) methods have been used to provide clues about stroke features and prognosis. However, the value of routine EEG in stroke patients without (suspected) seizures has been somewhat neglected. We aimed to assess this in a group of acute ischemic stroke patients in regard to short-term prognosis and basic stroke features. Methods : We assessed routine (10–20) EEG findings in 69 consecutive acute ischemic stroke patients without seizures. Associations between EEG abnormalities and NIHSS scores, clinical improvement or deterioration as well as MRI stroke characteristics were evaluated. Results : Mean age was 69 ± 18 years, 43 of the patients (62.3%) were men. Abnormal EEG was found in 40 patients (58%) and was associated with higher age ( p = 0.021). The most common EEG pathology was focal slowing (30; 43.5%). No epileptiform potentials were found. Abnormal EEG in general and generalized or focal slowing in particular was significantly associated with higher NIHSS score on admission and discharge as well as with hemorrhagic transformation of the ischemic lesion. Abnormal EEG and generalized (but not focal) slowing were associated with clinical deterioration ( p = 0.036, p = 0.003). Patients with lacunar strokes had no EEG abnormalities. Conclusions : Abnormal EEG in general and generalized slowing in particular are associated with clinical deterioration after acute ischemic stroke. The study demonstrates the value of routine EEG as a simple diagnostic tool in the evaluation of stroke patients especially with regard to short-term prognosis.